Influence Of Strategy Implementation On The Performance Of Maritime Cluster Firms In Kenya - Shimengah, Mulama Moses; Gathenya, Jane Wanjiku; Otieno, Romanus Odhiambo (Archives of Business Research, 2019)
The study of strategy implementation on the performance of maritime cluster firms has not been fully exhausted for economic growth despite its vast potential resources. In recent times, many countries near the oceans, seas, lakes, rivers and dams are exploiting their natural resources both off shore and on shore (for blue economy) with an aim of increasing their competitive advantage to create employment opportunities, wealth as new frontier by implementing maritime clusters strategy for economic growth and sustainability. This process helps them strengthen their national and regional competitiveness through clustering for their industrial development through processing, manufacturing and value addition of their products. This study seeks to stir up an academic curiosity in the field of maritime academic discipline and anticipates enhancing both policy and knowledge gaps in maritime related cluster firms. The findings of the research will be of importance to policy makers within the government and the maritime cluster firms as well as contribute to the body of knowledge as a reference material for future research works. The main objective of this study is to establish the influence of strategy implementation on performance of Maritime Cluster firms in Kenya and the specific objectives of this study are to establish the influence of strategic policies, strategic direction, organization structure, resource capability, technology innovation, firms’ size and years of operation on the performance of maritime cluster firms in Kenya. The research will allow collection of both quantitative and qualitative data and adopt descriptive research (statistical research) as well as inferential statistics designs in which variables of interest will not be controlled or manipulated. The target population of the study is 1386 maritime firms and the sample size of 94 firms which will be randomly selected as a basis for unit of analysis. Thus, the study will perform a pilot test to support reliability and validity tests based on 10% of the sample size of about 10 firms out of 94 firms which will not be included in the main study sample. Both primary and secondary data will be collected by use of questionnaires, structured interviews as instrument of data collection. Both factor analysis and correlation analysis will be used to determine the magnitude and direction of the association between research variables. The study will further perform hypothesis testing using ANOVA. The quantitative data collected will be analysed further through descriptive statistics such as mean, median, standard deviation supported by the statistical package for social science SPSS version 22 whereas the qualitative data will be analysed by use thematic analysis.